(untitled) (Brazilian Journal of Radiation Sciences, 2023)
The Brazilian coast of the terrace contains a wealth of evidence that can be used to explain the evolution of the coastline over the past 120k years. These studies include marine sediment geochronology based on dosimetry dating methods, in particular thermoluminescence. To determine the age of the terrace using luminescence dosimetry methods, it is necessary to decide on the exact mass fractions of 238U, 232Th, and 40K. These mass fraction values are used to calculate the annual dose rate of ionized radiation. In this context, in the present work, we studied eight marine sediment samples collected in the city of São Vicente on the coast of São Paulo state, Brazil, and determined the mass fractions of elements 238U, 232Th, and 40K by instrumental neutron activation analysis (INAA) and γ-ray spectroscopy. Linear regression mathematical methods are used to evaluate analytical methods accuracy. The results show a good correlation with a R2 value of more than 0.71. Therefore, it is possible to calculate the resulting mass fraction, calculate the dose rates of these sediments, and contribute to their date.